Plate H: Rockets mounted without sticks; water rockets; rockets mounted to lines - Siemienowicz, Kazimierz (Artis Magnae Artilleriae, 1650)
Fig. 60: Rocket mounted to a stick. Figs. 61, 62, 64, 65, and 73-76: Rockets. Fig. 63: Launching platform for rocket with wings, as in figure 61. Figs. 66-72: Water rockets.
Keywords: Rocketry; Artillery